Experimentation and uncertainty analysis for engineers - Coleman, Hugh W. (Wiley, 1989)
Contents: The seven chapters in the book can be divided into two parts. In the first part, chapters 1-4, we develop the methodology for properly considering the uncertainty in measured variables and the manner in which these uncertainties propagate into the uncertainty in the result of an experimental program. In the second part of the book, chapters 5-7 we present additional considerations in the design of experiments and illustrate the use of uncertainty analysis in the debugging, execution, data analysis , and reporting phases of an experiment.